Clinicopathological value of tumor-associated macrophages in adult classical Hodgkin lymphoma in Hawler city - Tenya Tariq Abdulhameed; Salah Abubakir Ali; Amin Aziz Bakir (Zanco Journal of Medical Sciences)
Background and objective: The aims of the present research were to study the clinicopathological features of adult classical Hodgkin lymphoma (cHL) in Hawler city and to evaluate the significance of immunohistochemical expression of CD68 positive tumor associated macrophage in the tumor microenvironment as a marker for prediction of malignant progression.